Hair tourniquet syndrome localized to the labia minora. - Yaich, S.; Masmoudi, A.; Souid, K.; Chaabouni, R.; Sallemi, K.; Charfi, S.; Boudayara, T.; Turki, H. (European Journal of Pediatric Dermatology, 2026)
Hair tourniquet syndrome (HTS) is a rare condition in which a hair or fiber encircles an appendage, leading to swelling, pain, and potentially ischemic necrosis. Uncommon, cases involving the female genitalia have been described. We report a case of HTS involving the labia minora in a 6-year-old girl, initially misdiagnosed, managed surgically, and confirmed by histological exam, in the absence of any context of sexual abuse. Early recognition of this condition is essential to prevent serious complications.